Peningkatan Kedisiplinan Belajar Matematika Siswa Melalui Strategi Pembelajaran Group Investigation Bagi Siswa Sekolah Dasar - Andi Maulana; Vikre Ahzari; Putra, Purniadi (Jurnal Pendidikan Dasar Islam, 2023)
The aim of this research is to examine the improvement of mathematics learning discipline for students in Class II at SDN 4 Pemangkat through the use of group investigation learning strategies. The method used in this research is a classroom action research method, which consists of two cycles. The primary data source used is a second-grade teacher, and the secondary data consist of several relevant journals and books. Data collection techniques include questionnaires, interviews, and documentation. Data analysis uses the flow method, namely data reduction, data presentation, and data verification. The results of the research show an increase in students' mathematics learning discipline, which can be seen from the increase in indicators including: 1) students starting lessons on time - before the action, it was 37.5%, in Cycle I it reached 50%, and after the action in Cycle II it was 87.5%; 2) students submitting assignments on time - before the action, it was 25%, in Cycle I it reached 40.62%, and after the action in Cycle II it became 81.25%; 3) students obediently following the learning process - before the action, it was 25%, in the first cycle of the class action it reached 40.62%, and after the action in the second cycle it became 75%; 4) only 15.62% of students were obedient in doing their homework before the action, in the first cycle of the class action it reached 34.37%, and after taking action in Cycle II it became 81.25%. Based on the description above, it can be concluded that implementing the cooperative group investigation strategy in mathematics learning can improve student learning discipline